Advances in the Application of Preclinical Models in Photodynamic Therapy for Tumor: A Narrative Review - Rong Yu; Ewetse Paul Maswikiti; Yang Yu; Lei Gao; Chenhui Ma; Huanhuan Ma; Xiaobo Deng; Na Wang; Bofang Wang; Hao Chen (MDPI AG, 2023)
Photodynamic therapy (PDT) is a non-invasive laser light local treatment that has been utilized in the management of a wide variety of solid tumors. Moreover, the evaluation of efficacy, adverse reactions, the development of new photosensitizers and the latest therapeutic regimens are inseparable from the preliminary exploration in preclinical studies. Therefore, our aim was to better comprehend the characteristics and limitations of these models and to provide a reference for related research. Methods: We searched the databases, including PubMed, Web of Science and Scopus for the past 25 years of original research articles on the feasibility of PDT in tumor treatment based on preclinical experiments and animal models. We provided insights into inclusion and exclusion criteria and ultimately selected 40 articles for data synthesis. Results: After summarizing and comparing the methods and results of these studies, the experimental model selection map was drawn. There are 7 main preclinical models, which are used for different research objectives according to their characteristics. Conclusions: Based on this narrative review, preclinical experimental models are crucial to the development and promotion of PDT for tumors. The traditional animal models have some limitations, and the emergence of organoids may be a promising new insight.